The Influence of TripAdvisor Reviews and Social Media Marketing Through Instagram on Brand Image at InterContinental Bali Sanur Resort - Sugiarta, Komang Rikha; Pitanatri, Putu Diah Sastri; Adyatma, Prastha (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the effect of TripAdvisor reviews and social media marketing through Instagram on brand image at InterContinental Bali Sanur Resort. Thus, it is hoped that this study can be used as a study and evaluation material for InterContinental Bali Sanur Resort to increase awareness of its brand image. In its implementation, this study took about four months with data collection techniques in this study being questionnaires and documentation studies. The number of samples in this study was 100 respondents and was distributed using Google Form. The results of this study indicate that there is a positive and significant influence, both partially and simultaneously, between TripAdvisor reviews and social media marketing through Instagram on brand image at InterContinental Bali Sanur Resort.